The patient suicide attempt - An ethical dilemma case study - Lin Jie (Elsevier, 2015)
Case description: Nurses face more and more ethical dilemmas during their practice nowadays, especially when they are taking care of the patient at end of life stage. The case study demonstrates an ethical dilemma when nursing staff are taking care of an end stage aggressive prostate cancer patient Mr Green who expressed the suicide thoughts to one of the nurses and ask that nurse keep secret for him in Brisbane, QLD, Australia. Ethical dilemma identification: The ethical dilemma is identified as "if the nursing staff should tell other health care team members about patient's suicide attempt without patient's consent". Analysis: To better solving this case and making the best moral decision, the ethical theory, the ethical principles and the Australian nurses' code of ethics values statement, the associated literature relative with this case are analyzed before the decision making. Ethical decision making: After consider all of the above factors, in this case, the best ethical decision for the patient is that the nurse share the information of Mr Green's suicide attempt with other health care professionals. Results: In Mr Green's case, the nurse chose to share the information of Mr Green's suicide attempt with other health care professionals. The nursing team followed the self-harm and suicide protocol of the hospital strictly, they maintained the effective communication with Mr Green, identified the factors which cause patient's suicide attempt, provided the appropriate nursing intervention to deal will these risk factors and collaborated with other health care professionals to prefect the further care. The patient transferred to a palliative care service with no sign of suicide attempt and other self-harm behaviors and passed away peacefully 76 days after discharged with his relatives and pastors accompany.